Formation of land capital in economic science: lessons for Ukraine - Dorosh, Y.; Bratinova, M.; Myronov, O. (Land Management, Cadastre and Land Monitoring, 2024)
It has been found that in the current institutional environment land resources are not considered capital in agriculture, and this requires a detailed justification of the mechanisms for their involvement in economic turnover to meet the investment needs of the agricultural sector of the economy. Approaches to understanding the essence of land capital in the current conditions of development of foreign and domestic economic science have been systematised. However, a broad definition of land capital in agriculture has not been provided. The study has confirmed that land plots intended for agricultural use can be considered capital only if they are used for economic activity and generate income or added value. It is emphasised that for the effective market capitalisation of agricultural land as a source of investment for the agricultural sector of the economy, it is necessary to improve the financial and economic mechanism of the process and properly reflect it in the information and analytical system. This system, in modern conditions, will become a tool for accounting and visualisation of spatial information, where indicators will reflect the efficiency or inefficiency of economic operations with land capital. They will serve as a basis for making management decisions, allowing timely and effective response to facts and phenomena. It is noted that a key factor in the capitalisation of land resources is an adequate assessment of their value in agriculture, which corresponds to modern market transformations. A new definition of the concept of "land capital" is proposed. A bibliometric analysis of the status of scientific support for the development of land capital in the world is carried out.Keywords: land capital, agricultural sector of the economy, land resources, real capital, natural capital, investment, mortgage, market capitalisation of agricultural land, food security, added value, agricultural land valuation.
Keywords: land capital; agricultural sector of the economy; land resources; real capital; natural capital; investment; mortgage; market capitalisation of agricultural land; food security; added value; agricultural land valuation